The effect of microporous vanadosilicate AM-6 thin films as photocatalysts for the degradation of methylene blue - Kuzyaka, Duygu; Galioglu, Sezin; Altın, İlknur; Sökmen, Münevver; Akata, Burcu (Elsevier BV, 2018)
Abstract In the current study, a new photocatalyst in thin film form exhibiting photocatalytic activity under visible light range was introduced. For that purpose, microporous vanadosilicate (AM-6, (Na,K)2VSi5O13) and silver nanoparticle (Ag0) incorporated vanadosilicate AM-6 thin films were investigated as photocatalysts for the photocatalytic decomposition of methylene blue (MB). To create different oxidation states of vanadium cation present in the ⋯V O V O V⋯ quantum wires within the framework of AM-6, two different molar compositions were used for thin film formation of vanadosilicate AM-6. The vanadosilicate AM-6 thin films demonstrated photocatalytic activity under ultraviolet (UV) and visible light irradiation. The microporous titanosilicate (ETS-10, (Na,K)2TiSi5O13) thin films, isomorph of vanadosilicate AM-6, were also used as photocatalysts for the degradation of MB for the comparison of photocatalytic effectiveness. When visible light irradiation is used for the photocatalytic decomposition of MB, the photocatalytic activity of AM-6 was significantly different with respect to ETS-10. The narrower band gap of AM-6 with respect to the band gap of ETS-10 and the presence of V5+ cations in the structure of AM-6 provided photocatalytic activity under visible light irradiation. It was found that, vanadosilicate AM-6 films with higher amount of V5+ ions possess better photocatalytic activity under visible light irradiation for the degradation of MB, which can be attributed to the presence of V5+ cations within the framework of AM-6. The presence of both V4+ and V5+ cations was characterized by XPS and Raman spectroscopy in the vanadosilicate AM-6 thin films. To enhance the photocatalytic activity of AM-6 thin films, Na+ and K+ ions of the as-synthesized AM-6 thin films were ion-exchanged with Ag+ ions and then reduced to Ag0 nanoparticles (NP) by using sodium borohydride (NaBH4) solution. The results showed that Ag0 NP incorporated AM-6 thin films showed an increased photocatalytic activity due to various reasons such as the role of metal nanoparticles as electron traps, surface plasmon resonance effect, and band-gap narrowing.
Keywords: 7. Clean energy